Comparison of evolutionary algorithms for LPDA antenna optimization - Lazaridis, PI; Tziris, EN; Zaharis, ZD; Xenos, TD; Cosmas, JP; Gallion, PB; Holmes, V; Glover, IA (Radio Science, 2016)
A novel approach to broadband log-periodic antenna design is presented, where some of the most powerful evolutionary algorithms are applied and compared for the optimal design of wire log-periodic dipole arrays (LPDA) using Numerical Electromagnetics Code. The target is to achieve an optimal antenna design with respect to maximum gain, gain flatness, front-to-rear ratio (F/R) and standing wave ratio. The parameters of the LPDA optimized are the dipole lengths, the spacing between the dipoles, and the dipole wire diameters. The evolutionary algorithms compared are the Differential Evolution (DE), Particle Swarm (PSO), Taguchi, Invasive Weed (IWO), and Adaptive Invasive Weed Optimization (ADIWO). Superior performance is achieved by the IWO (best results) and PSO (fast convergence) algorithms. NATO's Public Diplomacy Division in the framework of “Science for Peace”. Grant Number: SfP-984409 ORCA